Akuntan Manajemen sebagai Mitra Bisnis: Dampak Digitalisasi dan Keberlanjutan dalam Transformasi Peran - Dwinanda, Rizky Ridho; Utama, Anak Agung Gde Satia (Jurnal Akuntansi, 2025)
This study explores management accountants' evolving role and professional identity, focusing on the shift from traditional cost controllers to strategic business partners. Through a bibliometric analysis and systematic literature review (SLR), the study synthesizes findings highlighting the impact of digital transformation, including cloud-based ERP systems, AI, and business intelligence (BI), on the competencies and practices of management accountants. The analysis reveals that while digital tools enable increased participation in data-driven decision-making and sustainability efforts, challenges remain in overcoming traditional practices, cultural constraints, and the need for new skill sets. The findings also highlight management accountants' barriers to integrating sustainability into their roles. Despite these challenges, the study contributes to the literature by offering new insights into the professional identity transformation and providing practical guidance for organizations in facilitating this transition. The study further emphasizes the importance of enhancing education and training to equip management accountants with the necessary competencies for future roles. Future research is encouraged to address the gaps in technology adoption and organizational culture that hinder the full realization of this professional evolution.